THE EFFECT OF WALL STRETCHING EXERCISE ON PAIN PLANTAR FASCIITIS IN THE FLAG WAITING TROOPS IN SMAN 105 JAKARTA - Achwan, Achwan; Suprianto, Dodi; Kurniawati, Nia (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2023)
Background : Plantar Faciitis is heel pain caused by inflammation or irritation of the plantaris fascia. Plantar Faciitis is characterized by complaints of pain in the heel during the first step in the morning, when walking the pain will usually decrease. However, the pain may be felt again when standing for a long time or getting up from a sitting position. Plantar Fasciitis is associated with gait-related disability, the pain is usually at the front and base of the heel. The impact of plantar fasciitis is difficulty in daily activities, thus reducing productivity in daily life. Wall Stretching Exercise as one of the Physiotherapy interventions for Plantar Faciitis pain. Method: This research is pre-experimental with a pre-post test, the sample was selected using a purposive sampling method with a total of 19 people, pain measurement in this study used a visual analogue scale. Results: The normality test resulted in p> 0.05, which means the data distribution is not normal, so it was continued with the Wilcoxon test with the result p-value = 0.000 (p value < 0.05) so that H0 was rejected, which means there is a significant difference between before and after the Wall Stretching Exercise, so H0 was rejected, which means there was a difference between the Visual Analog Scale results before and after the Wall Stretching Exercise intervention was given. Conclusion: Wall Stretching Exercise has an effect on plantar fasciitis pain in flag-raising troops at SMAN 105 Jakarta.